A Compact Circular Patch Antenna for Wireless Network Applications - Nageswara Rao, L; Santhosh Kumar, V; Basha, M (International Journal of Engineering and Technology, 2018)
The compact double-band circular microstrip patch (MPA) with the etched slot for WLAN architecture is designed. A double recurrence circular patch design along space opening slot sustained with a transmission model is intended to acquire double recurrence task.Â  The designed antenna model comprises of circular patch and parasitic - slot resonator. The ground plane is arranged with a space opening resonator. By modifying structure parameters, the microstrip patch works at the upper band (5.2 GHz) and parasitic - opening works at bringing down band (2.4 GHz), the two resonators are emanating with two diverse radiation designs. Remembering the true objective to choose the execution of the designed model and the composed structure shows the arrival misfortune less than - 10 B and it is demonstrated with huge impedance coordinating, enhanced radiation example and great VSWR around 1 over the working groups. The investigated configuration is simulated and analyzed with HFSS. The suggested antenna model is reasonable for wireless LAN applications.Â Â